2012
DOI: 10.1111/bjh.12154
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of SRT501 (resveratrol) with bortezomib for patients with relapsed and or refractory multiple myeloma

Abstract: Additional Supporting Information may be found in the online version of this article:Fig S1. CD4 + T cells are highly effective inducers of CLL cell proliferation. Fig S2. Analysis of proliferative potential of CLL cells in in vitro cultures with respect to common risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(126 citation statements)
references
References 8 publications
0
125
0
1
Order By: Relevance
“…The predominant study finding was an unexpected renal toxicity and low efficacy of SRT501 with nausea and vomiting which could have resulted in disease progression and dehydration. This study has demonstrated an unacceptable safety profile and minimal efficacy in patients with relapsed/refractory multiple myeloma (Popat et al, 2013). At least two more clinical trials on colorectal cancer were completed but no published data was noted on the outcome.…”
Section: Natural Phytochemicals As Mtor Inhibitorsmentioning
confidence: 96%
See 1 more Smart Citation
“…The predominant study finding was an unexpected renal toxicity and low efficacy of SRT501 with nausea and vomiting which could have resulted in disease progression and dehydration. This study has demonstrated an unacceptable safety profile and minimal efficacy in patients with relapsed/refractory multiple myeloma (Popat et al, 2013). At least two more clinical trials on colorectal cancer were completed but no published data was noted on the outcome.…”
Section: Natural Phytochemicals As Mtor Inhibitorsmentioning
confidence: 96%
“…Unfortunately, a Phase II study of SRT501 (resveratrol) with bortezomib in patients w i t h r e l a p s e d a n d / o r refractory multiple myeloma has to be terminated recently (Popat et al, 2013). Out of 24 patients, 9 patients receiving SRT501 and bortezomib were withdrawn from the study, mainly due to serious adverse reactions.…”
Section: Natural Phytochemicals As Mtor Inhibitorsmentioning
confidence: 99%
“…It is important to note that there is some evidence that resveratrol may have adverse effects in certain cancer patients. In a phase II clinical trial involving relapsed or refractory multiple myeloma patients, resveratrol at a dose of 5 g per day caused adverse events (including nausea, diarrhea, fatigue, and renal toxicity), which may have contributed to the death of one patient and caused the investigators to prematurely end the study (Popat et al 2013). The authors note that this high dose has been shown to be safe in other clinical trials in healthy patients.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Subsequent clinical trials are currently investigating this dose limit [307,310]. Resveratrol's poor bioavailability is a significant issue with regard to extrapolating its effects to humans, and various approaches have been created to enhance its bioavailability [311], including consuming it with various foods [312], using it in combination with an additional phytochemical piperine [313], and using a prodrug approach [314], micronized powders [315,316], or nanotechnological formulations [317][318][319].…”
Section: Clinical Trials With Resveratrolmentioning
confidence: 99%